2020
DOI: 10.1016/j.cell.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Atlas of Primate Ovarian Aging

Abstract: Highlights d Single-cell transcriptomic roadmap of NHP ovarian aging d Molecular signatures revealed for NHP oocytes at stepwise developmental stages d Cell-type-specific inactivation of antioxidant genes in aged monkey and human ovaries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
357
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(376 citation statements)
references
References 99 publications
19
357
0
Order By: Relevance
“…Single cell gene expression analyses bridge the interface of cell biology, pathology and gene regulation. These analyses are transforming our understanding of intra-tissue heterogeneity in development, normal tissue homeostasis, and disease alike (Cao et al, 2019;Wang et al, 2020). Using single cell RNA-seq performed with the 10x Genomics platform, we generated a cellular atlas of the human fallopian tube in cancer-free women, and identified the transcriptional networks driving the expression programs of 13 major cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell gene expression analyses bridge the interface of cell biology, pathology and gene regulation. These analyses are transforming our understanding of intra-tissue heterogeneity in development, normal tissue homeostasis, and disease alike (Cao et al, 2019;Wang et al, 2020). Using single cell RNA-seq performed with the 10x Genomics platform, we generated a cellular atlas of the human fallopian tube in cancer-free women, and identified the transcriptional networks driving the expression programs of 13 major cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, localization of CYP17A1 shifted from exclusively the theca interna in control mice to patches in the interstitial stroma in DHT-treated mice, supporting a potential role for the stroma in androgen production following certain perturbations (Candelaria et al 2019). Singlecell RNA sequencing studies have also demonstrated subpopulations of stromal cells expressing CYP17A1 and STAR (Wagner et al 2020, Wang et al 2020. Although stromal cells have demonstrated varied hormone production and responsiveness, definitive characterization of these dynamics and their functional significance remains to be established (Fig.…”
Section: R33mentioning
confidence: 95%
“…The stromal cell distribution is also likely to be affected by cyclic structural changes, as follicles grow and ovulate and corpora lutea develop. Changes are also evident over the reproductive lifespan, including increases in fibrotic collagen as demonstrated in aging murine and primate ovaries (Briley et al 2016, Wang et al 2020. Some possible cellular markers that have been identified include COUP-TFII and/or ARX (Hummitzsch et al 2013, Rotgers et al 2018.…”
Section: Incompletely Characterized Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is associated with numerous processes including mitochondrial, oxidative stress and uncontrolled inflammation can negatively affect female fertility (4).…”
mentioning
confidence: 99%